"Dignity": A central construct in nursing home staff understandings of quality continence care. Issue 11 (6th April 2018) - Ostaszkiewicz, Joan; Tomlinson, Emily; Hutchinson, Alison M
Abstract : Aims and objectives: To explore nursing home staff members' beliefs and expectations about what constitutes "quality continence care" for people living in nursing homes. Background: Most nursing home residents require assistance to maintain continence or manage incontinence. Best practice guidelines promote active investigation of incontinence, treatment of underlying potentially reversible causes, and initial conservative interventions to prevent, minimise and/or treat incontinence. Despite research showing the positive benefits of implementing active interventions, translating the findings of research into practice in nursing homes has been modest. Understanding the perspectives of individuals who provide continence care may help bridge the gap between evidence and practice. Design: A qualitative exploratory descriptive design. Methods: Qualitative interviews were conducted with 19 nursing home staff: eight registered nurses, four enrolled nurses and seven personal care workers working in a nursing home in Australia between 2014–2015. Data were analysed inductively to identify themes and subthemes that described and explained staff beliefs about quality continence care in nursing homes. Findings: Participants' understanding and expectations about quality continence care were linked to beliefs about incontinence being an intractable and undignified condition in nursing homes. The key theme to emerge was "protecting residents' dignity" which was supported by the following six subthemes: (i) using pads, ii) providing privacy, (iii) knowing how to "manage" incontinence, (iv) providing timely continence care, (v) considering residents' continence care preferences and (vi) communicating sensitively. Conclusion: The findings provide new insight into the basis for continence care practices in nursing homes. Education about continence care should challenge beliefs that limit continence care practice to cleaning, containing and concealing incontinence. There is a need for a multidimensional framework that is informed by social, psychological and biomedical research about incontinence, research about the fundamental elements of care, care‐dependent individuals' expectations about care, and values about dignity and care. Relevance to clinical practice: The in‐depth exploration led to an understanding of the basis for continence care practices that centre on cleaning, containing and concealing residents' incontinence in some nursing homes. There is a need to review the quality of education for the aged care workforce about incontinence to ensure it equips them with a broad understanding of the fundamentals of care and how to enact dignity in continence care through a resident‐centred approach.